STUDI PELEPASAN TEOFILIN DARI CANGKANG KAPSUL ALGINAT-KITOSAN MENGGUNAKAN TRIPOLIFOSFAT SEBAGAI CROSSLINKER - Cut Intan Annisa Puteri; Rahmadani Rahmadani; Chairunnisa Anggi (Universitas Haji Sumatera Utara, 2022)
The modified formulation provides a fairly effective way to overcome the problem of bioavailability and results in increasing drug reactions and minimizing fluctuations in blood levels during release. The crosslinker in this study is sodium tripolyphosphate (Na-TPP) which is considered the best binding agent and can produce prolonged drug release. The purpose of this study was to determine the profile of theophylline release from the capsule shell of the alginate-chitosan matrix combination using the crosslink method. The capsule shell was made with the ratio of the percentage of alginate ; chitosan; The TPP are F1 (2%; 2%; 4%) and F2 (4%; 2%; 4%). The difference in percentage is intended to determine the ratio of the most optimal levels of releasing theophylline. The results obtained showed that theophylline capsules from formulas F1 and F2 could release the drug slowly and for a long time to the artificial intestinal fluid pH 7.4 for 8 hours for formula F1 and for 12 hours for formula F2 with a cumulative percentage of release of 99.75%.